(untitled) (The Journal of Psychology and Sociology, 2014)
The article describes the conditions and factors for the genesis of youth subculture. Based on the analysis different conceptual periods, the authors give several definitions of the concept of «youth subculture» that contributes to the understanding of other cultural and worldview traditions. The article pointed out that with the emergence of post-modern trends in social and cultural development of society, there is a new understanding of youth subculture with characteristics such as pluralism, multiplicity, uncertainty, fragmentation, variability, and eclecticism. The authors conclude that the West European model of youth subcultures can not be fully applied in Kazakhstan realities, their cultural styles are indicators of leisure-time activity of Kazakhstani youth.